Qualitative Study on the Toxic Triangle Integration of Leadership Ostracism - Chen, Zhixia; Sun, Mei (Frontiers in Psychology, 2021)
Leadership ostracism widely exists in all types of organizations, yet specific study regarding this trend is limited. With this study we explore the influencing mechanisms of leadership ostracism through case interview based on literature analysis and grounded theory. Results show that leadership ostracism is the integration of a triadic interaction process between subordinate performance, leadership characteristics, and organizational environment. Based on Padilla’s destructive leadership toxic triangle model, we constructed a toxic triangle model of leadership ostracism. Through comparison, we found that these two triad models overlap in the areas of narcissism and power consciousness of supervisors, the self-concept of subordinates, and the management system of situational factors, indicating that leadership ostracism is itself a type of destructive leadership. In addition, the uniqueness and differences in leadership ostracism are reflected in the model, including stereotypes and results orientation of supervisors, political skills, job performance and cognitive style of subordinates, the power distance, Chaxu climate and organizational politics of the situational elements. Theoretical and practical implications are discussed in the research field that provide prospects for future orientation.